An IoT Based Interface for the Smart Watering of Plants using Soil Moisture Sensor - Hemalatha, K; Likitha, L G; Sireesha, N; Usharani, A (IRO Journal on Sustainable Wireless Systems, 2023)
Water plays a significant role in the growth of plants. Under watering and Over watering of plants may slow down the transpiration and photosynthesis processes. Hence proper watering is essential for the better growth of the plant. Internet of Things (IoT) provides the solution to the proper watering of plants. Hence, this study has developed an interface using soil moisture sensor and Ardunio for the monitoring of soil moisture of the plants, which help to water the plants properly. Based on the moisture data captured from the soil moisture sensor watering suggestions can be provided for the better growth of the plants. This interface helps to water the plant when it needs water and also it will be helpful for the optimum water utilization.